1.Pomnóż i zredukuj wyrazy podobne :
a) (x² + 3x + 3)(x - 1) - (x + 3)(x - 2)
b) (a² + 3a + 2)(a - 3) - (a - 1)(3a² - a + 1)
c) 3(x + y) + x² - y² + (x + y)(2x - 3y)

2. Zapisz iloczyn w postaci sumy :
a) 3x(x + 1)(x - 3)
b) 5(x - 2)( x + 3)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T19:48:22+01:00
Zadanie 1
a) (x² + 3x + 3)(x - 1) - (x + 3)(x - 2)
x³-x²+3x²-3x+3x-3-(x²-2x+3x-6)= x³-x²+3x²-3x+3x-3-x²+2x-3x+6= =-x+x³+x²+3

b) (a² + 3a + 2)(a - 3) - (a - 1)(3a² - a + 1)= a³-3a²+3a²-9a+2a-6 - (3a³-a²+a-3a²-a-1) = a³-3a²+3a²-9a+2a-6 - 3a³+a²-a+3a²+a+1 = =-2a³+4a²-7a-5

c) 3(x + y) + x² - y² + (x + y)(2x - 3y) =3x+3y+x²-y²+2x²-3xy+2xy-3y²=
=-xy-4y²+3x²+3x+3y

zadanie 2
a) 3x(x + 1)(x - 3)=3x(x²-3x+x-3)= 3x³-9x²+3x²-9x=3x³-6x²-9x
b) 5(x - 2)( x + 3)=5(x²+3x-2x-6)=5x²+15x-10x-30=5x²+5x-30